THE NEUROENDOCRINOLOGY OF CHRONIC STRESS: EVALUATING THE CLINICAL EFFICACY OF ASHWAGANDHA (WITHANIA SOMNIFERA) ON SERUM CORTISOL AND PSYCHOSOCIAL WELL-BEING - Julia Weronika Mieszkowska; Norbert Grabias; Jędrzej Piotrowski; Paulina Jarząbek; Maria Rajkowska; Aleksandra Włodarczyk; Radosław Gryko; Bernard Myszewski; Anna Kinga Tejchma; Łukasz Dominik Woźniak (International Journal of Innovative Technologies in Social Science, 2026)
Background: Chronic stress is a pervasive global health challenge characterized by the dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis. This neuroendocrine imbalance leads to elevated serum cortisol, which subsequently triggers systemic disruptions in reproductive health, metabolic homeostasis, and psychosocial well-being. Withania somnifera (Ashwagandha), a premier adaptogen, is increasingly recognized for its ability to modulate these multifaceted stress responses. Objective: This review evaluates the clinical efficacy of Ashwagandha in reducing serum cortisol and enhancing well-being, while synthesizing its systemic impact on the reproductive, metabolic, immune, and sleep systems. Methods: A comprehensive synthesis of over 48 contemporary sources, including randomized controlled trials (RCTs) and meta-analyses, was conducted to assess hormonal, psychometric, and physiological outcomes. Results: Evidence consistently demonstrates that standardized Ashwagandha extracts (240–600 mg/daily) reduce serum cortisol levels by 11% to 32%. These changes correlate with significant improvements in anxiety (PSS-10, HAM-A) and sleep parameters, specifically reduced sleep onset latency and enhanced efficiency. Beyond the HPA axis, Ashwagandha restores the hypothalamic-pituitary-gonadal (HPG) axis, significantly improving sperm concentration and testosterone levels in males. Metabolic benefits include modest weight reduction and improved insulin sensitivity, while ergogenic effects manifest as increased VO2max and accelerated muscular recovery. Furthermore, the herb exhibits immunomodulatory properties and subtle influences on thyroid indices (HPT axis), alongside emerging geroprotective potential. While generally safe, clinical monitoring for thyroid dysfunction is advised. Conclusion: Ashwagandha functions as a robust multi-systemic regulator. Its ability to restore homeostatic balance across the HPA, HPG, and HPT axes justifies its integration into evidence-based protocols for stress management, metabolic health, and physical vitality.